Hermeneutic Interpretation of Implicit Cultural Meanings in News Headlines: Evidence from English- and Uzbek-Language Media - Alimova, Kamola Tursunovna (The Lingua Spectrum, 2026)
This article reviews and operationalizes a hermeneutic approach to uncovering implicit cultural meanings in news headlines in English- and Uzbek-language media. Building on philosophical hermeneutics, the study treats headline understanding as a situated interpretive act shaped by readers’ pre-understandings and historically formed “horizons,” and it models meaning construction as movement within the hermeneutic circle between text and context. To make implicitness analytically traceable, the paper integrates hermeneutic reading with pragmatic tools for presupposition and implicature and with media-framing analysis. Headlines are approached as genre-specific, relevance-oriented prompts that guide readers toward an “optimal” interpretive context while compressing information in ways that systematically rely on shared cultural knowledge. A qualitative comparative procedure is proposed to identify recurrent types of cultural implicitness (ritual-calendar references, institutional hierarchy cues, collectivizing deixis, evaluative registers, and culture-specific naming conventions) and to explain how these resources produce different interpretive trajectories for insider vs. outsider audiences. The article argues that cross-linguistic headline analysis benefits from hermeneutics because it makes visible not only what is said, but what must already be known for the headline to “work” as a communicative act.